Effects of temperature and water potential on seed germination characteristics in Safflower (Carthamus tinctorius L.) Sofeh var. - R. Ostadian Bidgoly; H.R. Balouchi; E. Soltani; A. Moradi (علوم و فناوری بذر ایران, 2017)
There is a little information about the effects of temperature and water potential on safflower. In order to study the effects of temperature and water potential on seed germination characteristics of safflower (Carthamus tinctorius L.), an experiment as combined analysis was conducted base on a completely randomized design with 4 replications by 25 seeds in laboratory of seed technology at Yasouj University in 2015. The factors included temperature (5, 10, 15, 20, 25, 30, 35, 40 and 45 oC) and water potential (0, -0.2, -0.4, -0.6, -0.8, -1, -1.2, -1.4 and -1.6 MPa). The percentage and rate of germination, root length, shoot length, ratio of root length to shoot length and seedling vigor index were measured in this experiment. The results of analysis of variance showed that main effects of temperature and water potential and interactions were significant on all indicators of germination at 1% probability level. Also, by decreased water potential, germination percentage and germination rate reduced. At 5 oC and at zero potential germination percentage was 98% while the potential of -1.6 MPa germination percentage dropped to zero. At 35 oC and at zero potential germination percentage was 95% while the using potential of -1.6 MPa germination percentage decreased to 1%.  By increasing the temperature up to 20oC increasing germination percentage and germination rate detected and afterwards reduced.